Zero-energy-consumption cooling fabric with multilevel structure based on wavelength conversion and preparation method of zero-energy-consumption cooling fabric

By designing a multi-stage structure based on wavelength conversion on the sunshade cloth, combining the high-reflection layer, the ultraviolet-visible wavelength conversion layer and other functional layers, the problems of poor cooling effect and single function of the sunshade cloth in the existing technology are solved, and the multifunctional zero-energy cooling effect is achieved.

CN119736803APending Publication Date: 2025-04-01HUAZHONG UNIV OF SCI & TECH +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411924196.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The prior art is difficult to achieve a zero-energy cooling effect with super-strong solar spectrum reflection regulation capability and multifunctional functions in the sunshade cloth, and there are problems such as poor flexibility and relatively single functions.

Method used

Using a multi-stage structural design based on wavelength conversion, a multi-functional cooling fabric is formed by forming a high reflective layer and an ultraviolet-visible wavelength conversion layer on the fabric, and combining waterproof, acid-proof, alkali-proof and anti-corrosion coatings.

Benefits of technology

It has achieved excellent multi-functional integration such as zero energy consumption cooling, waterproofing, corrosion resistance, and ultraviolet aging resistance, and is suitable for various scenarios such as automotive sunshade cloth and tent cloth.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005209008900000131
    Figure BDA0005209008900000131
  • Figure BDA0005209008900000141
    Figure BDA0005209008900000141
  • Figure HDA0005209009090000011
    Figure HDA0005209009090000011
Patent Text Reader

Abstract

The invention relates to the field of functional textiles, in particular to a multistage-structure zero-energy-consumption cooling fabric based on wavelength conversion and a preparation method of the multistage-structure zero-energy-consumption cooling fabric based on wavelength conversion, the multistage-structure zero-energy-consumption cooling fabric prepared through the method is of a multistage structure, and particularly relates to a high-reflection layer with high-refractive-index micro-nano particles. The ultraviolet-visible wavelength conversion layer with the ultraviolet-visible wavelength conversion particles and the functional layer with the waterproof coating, the acid-proof coating, the alkali-proof coating, the anticorrosive coating and other coatings jointly form the cooling fabric with the super-strong solar spectrum reflection regulation and control capacity, and meanwhile the fabric can achieve the functions of water resistance, corrosion resistance, ultraviolet aging resistance and the like. The fabric is a multifunctional fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of functional textiles, and in particular to a multi-level structure zero-energy cooling fabric based on wavelength conversion and a preparation method thereof. Background Art

[0002] With the frequent occurrence of extreme high temperature weather caused by global warming, cars are inevitably damaged by outdoor high temperature and sunlight exposure, which leads to health problems such as sunburn and heatstroke for people in the car, aging and failure of in-car equipment, and increased energy consumption of air conditioning cooling. However, most sunshade fabrics have limited cooling effect in outdoor direct sunlight environment, and cannot block the huge solar radiation energy input, which leads to the increase of temperature in the car and is difficult to meet the outdoor cooling demand. At present, people have higher and higher requirements for textiles, among which functional textiles are widely concerned and loved by people because they can improve solar radiation and temperature in the car.

[0003] A shading and cooling fabric is disclosed in the patent document with publication number CN218906556U. The shading and cooling fabric includes a base fabric, a first adhesive layer and a cooling layer sequentially stacked on the surface of the base fabric, and the surface of the cooling layer away from the first adhesive layer is the light incident side. The shading and cooling fabric has excellent shading performance and excellent radiation cooling function. The above method effectively regulates the transmittance of sunlight in the 0.3μm-2.5μm band, but does not have other functions and has a single function.

[0004] The patent document with the publication number CN219214343U discloses a new type of sunshade cloth with a multi-layer structure, including a surface layer, an inner layer and a bottom layer, a combination layer is arranged between the surface layer and the inner layer, and an insulation layer, a silver adhesive tape layer and a corrugated separation layer are arranged between the inner layer and the bottom layer in sequence, the top of the heat insulation layer is connected with a silver adhesive tape layer, the top of the silver adhesive tape layer is provided with a corrugated separation layer, and the top of the corrugated separation layer is connected with the bottom of the inner layer. The sunshade cloth prepared by the above method has good UV resistance, and by providing a metal mesh graphene composite layer and a wear-resistant layer, the sunshade cloth can be fully protected. However, there are problems such as poor flexibility and relatively single function.

[0005] Publication number CN220264803U discloses a flame-retardant blackout cloth, which realizes flame-retardant function through the liquid spraying assembly of the storage box. The blackout cloth assembly is stored in the inner cavity of the storage box. During the storage process, the water-free cleaning liquid is sprayed onto the outer surface of the blackout cloth assembly through the provided liquid spraying assembly. Under the action of friction, the first friction roller and the second friction roller are forced to rotate, thereby cleaning the dirt on the surface of the blackout cloth assembly, achieving a self-cleaning effect, and facilitating the storage of the blackout cloth assembly. However, the equipment of this method is relatively bulky, the operation is complicated, and the ability to regulate spectral performance is limited.

[0006] Publication number CN215970400U discloses an anti-ultraviolet light-shielding cloth. An antistatic layer is fixedly connected to the upper surface of the light-shielding cloth layer, and an insulation layer, an anti-ultraviolet layer and a silver adhesive tape layer are fixedly connected to the upper surface in sequence. The anti-ultraviolet light-shielding cloth is prepared by a coating process to form a silver adhesive tape layer with functions such as light shielding and radiation protection. The anti-ultraviolet layer is treated by immersing in an ultraviolet reflective agent, mainly absorbing ultraviolet rays and converting energy, thereby achieving the purpose of preventing ultraviolet radiation, thereby achieving a good anti-ultraviolet effect.

[0007] The sunshade cloth currently on the market has good UV protection function, but the actual cooling effect is poor, and it cannot effectively prevent UV damage to people / equipment in the car. In addition, the addition of UV protection materials will reduce the strength of the fabric fiber, facing the problem of being unable to be prepared on a large scale. The post-processing method to prepare sunshade cloth is more efficient and easy to operate. Summary of the invention

[0008] Therefore, there is a lack of zero-energy cooling fabrics that have both super-strong solar spectrum reflection and control capabilities and multi-functions through multi-level structural design, and achieve excellent zero-energy cooling, waterproof, corrosion resistance, UV aging resistance and other multi-function integration, which is suitable for various indoor and outdoor scenes such as car sunshade cloth, tent cloth, glass house sunshade cloth, architectural decoration cloth, etc. Based on the above defects of the existing technology, it is necessary to improve it.

[0009] In order to solve the above problems, the present application provides a multi-level structure zero-energy cooling fabric based on wavelength conversion and a preparation method thereof, the preparation method comprising:

[0010] 1. A method for preparing a fabric, comprising the steps of:

[0011] dissolving the organic polymer in an organic solvent to obtain a conjugate solution;

[0012] Adding high refractive index micro-nano particles and a modifier to the conjugate solution in sequence to obtain a high reflective layer solution;

[0013] Adding UV-visible wavelength conversion particles and a modifier to the conjugate solution in sequence to obtain a UV-visible wavelength conversion layer solution;

[0014] The high reflection layer solution and the ultraviolet-visible wavelength conversion layer solution are subjected to ultrasonic treatment respectively;

[0015] Applying the ultrasonically treated high-reflection layer solution on the fabric by scraping, and forming a high-reflection layer after drying and curing;

[0016] The ultraviolet-visible wavelength conversion layer solution after ultrasonic treatment is scraped onto the high reflection layer, and after drying and curing, an ultraviolet-visible wavelength conversion layer is formed.

[0017] 2. The method according to item 1, wherein a dye is also scraped on the ultraviolet-visible wavelength conversion layer, and the coating forms a visible colored layer after drying and curing.

[0018] 3. The method according to item 1, wherein one or more of waterproof coating, acid-proof coating, alkali-proof coating and anti-corrosion coating are scraped on the ultraviolet-visible wavelength conversion layer to form other functional layers.

[0019] 4. The method according to item 2, wherein one or more of waterproof coating, acid-proof coating, alkali-proof coating and anti-corrosion coating are scraped on the visible colored layer to form other functional layers.

[0020] 5. The method according to item 1, wherein the particle size of the high refractive index micro-nanoparticles is 10 nm to 3 μm.

[0021] 6. The method according to item 1, wherein the mass of the high refractive index micro-nanoparticles accounts for 15 to 35 wt % of the mass of the high reflective layer.

[0022] 7. The method according to item 1, wherein the mass of the ultraviolet-visible wavelength conversion particles accounts for 3 to 7 wt % of the mass of the ultraviolet-visible wavelength conversion layer.

[0023] 8. The method according to item 1, wherein the high refractive index micro-nanoparticles are selected from one or more of titanium dioxide, silicon dioxide, zinc oxide, silicon carbide, silicon nitride, zinc sulfide, aluminum oxide, iron oxide, boron nitride, magnesium oxide, barium sulfate, barium carbonate and aluminum silicate materials.

[0024] 9. The method according to item 1, wherein the ultraviolet-visible wavelength conversion particles are selected from one or more of fluorescein isothiocyanate, Oregon green, carboxy naphthofluorescein, rhodamine, oxadiazoles and their derivatives, triazoles and their derivatives, rhodamine and their derivatives, coumarin derivatives, 1,8-naphthalimide derivatives, pyrazoline derivatives, triphenylamine derivatives, porphyrin compounds, carbazole, pyrazine, thiazole derivatives and perylene derivatives.

[0025] 10. The method according to item 1, wherein the modifier is selected from one or more of sodium secondary alkyl sulfonate, sodium fatty acid methyl ester ethoxylate sulfonate, sodium fatty acid methyl ester sulfonate, sodium dioctyl succinate sulfonate, sodium dodecylbenzene sulfonate, sodium glycocholate, and sodium taurocholate.

[0026] 11. The method according to item 1, wherein the organic polymer is selected from one or more of polyacrylic acid, polytetrafluoroethylene, polyvinylidene fluoride, polydimethylsiloxane, polyurethane, polypropylene, polyethylene and polyamide.

[0027] 12. The method according to item 2, wherein the dye is selected from one or more of medium chrome yellow, red iron oxide, iron yellow, iron blue, iron green, iron black, toluidine red, scarlet powder, and molybdate chrome orange.

[0028] 13. A fabric comprising:

[0029] Fabric substrate;

[0030] Highly reflective layer;

[0031] UV-visible wavelength conversion layer;

[0032] Visible colored layer; and

[0033] Other functional layers.

[0034] 14. The fabric according to item 13, wherein

[0035] The thickness of the high reflective layer is 15 to 400 μm;

[0036] The thickness of the ultraviolet-visible wavelength conversion layer is 15 to 400 μm;

[0037] The thickness of the visible colored layer is 15 to 400 μm;

[0038] The thickness of the other functional layer is 15-400 μm.

[0039] 15. The fabric according to item 13, wherein the fabric substrate, the high reflective layer, the ultraviolet-visible wavelength conversion layer, the visible colored layer and other functional layers are arranged in sequence from bottom to top.

[0040] 16. The fabric according to item 13, wherein the other functional layer has at least one or two or more of a waterproof function, an acid resistance function, an alkali resistance function and an anti-corrosion function.

[0041] 17. The fabric according to item 13, wherein the mass of the high refractive index micro-nanoparticles in the high reflective layer accounts for 15 to 35 wt% relative to the mass of the high reflective layer.

[0042] 18. The fabric according to item 13, wherein the mass of the ultraviolet-visible wavelength conversion particles in the ultraviolet-visible wavelength conversion layer accounts for 3 to 7 wt % relative to the mass of the ultraviolet-visible wavelength conversion layer.

[0043] 19. The fabric according to any one of items 13 to 18, which is prepared by the method according to any one of items 1 to 12.

[0044] 20. A fabric, wherein the fabric is prepared by the method described in any one of items 1 to 12.

[0045] 21. The fabric as described in any one of items 13 to 20 is used for cooling in automobile sunshades, tent fabrics, glass house sunshades, and building decorative fabrics.

[0046] The multi-level structure zero-energy cooling fabric based on wavelength conversion provided in the present application has a multi-level structure, specifically involving a high-reflection layer with high-refractive index micro-nano particles, an ultraviolet-visible wavelength conversion layer with ultraviolet-visible wavelength conversion particles, and a functional layer of coatings such as waterproof coatings, acid-proof coatings, alkali-proof coatings, and anti-corrosion coatings, which together constitute a cooling fabric with super-strong solar spectrum reflection and regulation capabilities. The fabric can also achieve functions such as waterproofing, corrosion resistance, and ultraviolet aging resistance, and is a multifunctional fabric. BRIEF DESCRIPTION OF THE DRAWINGS

[0047] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0048] Figure 1 This is a schematic diagram of the structure of the multi-level structure zero-energy cooling fabric prepared in this application.

[0049] Figure 2 The wavelength conversion data of the ultraviolet-visible wavelength conversion particles used in Example 3 of the present application.

[0050] Figure 3 This is a SEM of the high reflective layer of the multi-level structure zero-energy cooling fabric prepared in Example 3 of the present application.

[0051] Figure 4 The reflectivity data of the multi-level structure zero-energy cooling fabric prepared in Examples 3, 5, 6 and 7 of the present application. DETAILED DESCRIPTION

[0052] The specific embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the specific embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present application and to fully convey the scope of the present application to those skilled in the art.

[0053] It should be noted that certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that technicians may use different nouns to refer to the same component. This specification and claims do not use the difference in nouns as a way to distinguish components, but use the difference in the functions of the components as the criterion for distinction. As mentioned throughout the specification and claims, "including" or "comprising" is an open term, so it should be interpreted as "including but not limited to". The subsequent description of the specification is a preferred embodiment of the implementation of the present application, but the description is based on the general principles of the specification and is not used to limit the scope of the present application. The scope of protection of the present application shall be determined by the attached claims.

[0054] The particle size test in the present invention adopts laser diffraction technology, and mainly uses Mastersizer3000+Ultra laser particle size analyzer to test the particle size and particle size distribution of the material. It achieves this by measuring the light intensity scattered when the laser beam passes through the dispersed particles. These data are then analyzed to calculate the particle size that produces the scattering model. The micro-nano particle samples to be tested must be pretreated to ensure that they are completely dispersed before they can be tested on the machine. The duration of background measurement using Mastersizer 3000+Ultra laser particle size analyzer is generally 10s; the duration of sample measurement is generally 10-12s, and the number of tests is generally 3 times. The equipment measurement results are shown as DI (intensity distribution) by default, and DI50 is selected as the particle size data of the corresponding micro-nano particles.

[0055] In this application specification, "high reflective layer" is also known as "optical metamaterial high reflective layer". "Optical metamaterial" is an artificial material containing nanostructures. The special structure gives it special optical properties. Their structure is obtained from at least two different materials (usually including metal and dielectric material).

[0056] In the present application, the "textile substrate" is one or more selected from woven fabric, knitted fabric and non-woven fabric.

[0057] The present application provides a method for preparing a fabric, the steps of which include:

[0058] The organic polymer is dissolved in an organic solvent to obtain a conjugate solution; high refractive index micro-nano particles and a modifier are sequentially added to the conjugate solution to obtain a high reflective layer solution; ultraviolet-visible wavelength conversion particles and a modifier are sequentially added to the conjugate solution to obtain an ultraviolet-visible wavelength conversion layer solution; the high reflective layer solution and the ultraviolet-visible wavelength conversion layer solution are ultrasonically treated respectively; the high reflective layer solution after ultrasonic treatment is scraped on the fabric, and a high reflective layer is formed after drying and curing; the ultraviolet-visible wavelength conversion layer solution after ultrasonic treatment is scraped on the high reflective layer, and a ultraviolet-visible wavelength conversion layer is formed after drying and curing.

[0059] In a specific embodiment of the present application, a dye is also scraped on the ultraviolet-visible wavelength conversion layer, and the coating forms a visible colored layer after drying and curing.

[0060] In a specific embodiment of the present application, other functional layers are continuously coated on the visible colored layer.

[0061] In a specific embodiment of the present application, when a visible colored layer is not needed, other functional layers are directly scraped on the ultraviolet-visible wavelength conversion layer.

[0062] In a specific embodiment of the present application, the other functional layer may be another functional layer having a waterproof function and composed of a waterproof coating.

[0063] In a specific embodiment of the present application, the other functional layer may be another functional layer composed of an acid-proof coating and having an acid-proof function.

[0064] In a specific embodiment of the present application, the other functional layer may be another functional layer composed of an alkali-proof coating and having an alkali-proof function.

[0065] In a specific embodiment of the present application, the other functional layer may be another functional layer having an anti-corrosion function and composed of an anti-corrosion coating.

[0066] In a specific embodiment of the present application, the other functional layers are composites of two or more of waterproof coatings, acid-proof coatings, alkali-proof coatings and anti-corrosion coatings; it should be understood that the mass proportion of the above coatings relative to other functional layers is not fixed, and the mass proportion of each coating is adjusted accordingly according to the usage scenario.

[0067] In a specific embodiment of the present application, the particle size of the high refractive index micro-nano particles is 10nm to 3μm, for example, it can be 10nm, 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm, 150nm, 200nm, 250nm, 300nm, 350nm, 400nm, 450nm, 500nm, 550nm, 600nm, 650nm, 700nm, 750nm, 800nm, 850nm, 900nm, 950nm, 1000nm, 1050nm, 1100nm, 1150nm, 1200nm, 1250nm, 130 0nm, 1350nm, 1400nm, 1450nm, 1500nm, 1550nm, 1600nm, 1650nm, 1700nm, 1750nm, 1800nm, 1850nm, 1900nm, 1950nm, 2000nm, 2050nm, 2100nm, 2150n m, 2200nm, 2250nm, 2300nm, 2350nm, 2400nm, 2450nm, 2500nm, 2550nm, 26 00nm, 2650nm, 2700nm, 2750nm, 2800nm, 2850nm, 2900nm, 2950nm, 3000nm.

[0068] In a specific embodiment of the present application, the mass of the high refractive index micro-nano particles relative to the mass of the high reflective layer is 15 to 35 wt%, for example, 15 wt%, 15.5 wt%, 16 wt%, 16.5 wt%, 17 wt%, 17.5 wt%, 18 wt%, 18.5 wt%, 19 wt%, 19.5 wt%, 20 wt%, 20.5 wt%, 21 wt%, 21.5 wt%, 22 wt%, 22.5 wt%, 23 wt%. t%, 23.5wt%, 24wt%, 24.5wt%, 25wt%, 25.5wt%, 26wt%, 26.5wt%, 27wt%, 27.5wt%, 28wt%, 28.5wt%, 29wt %, 29.5wt%, 30wt%, 30.5wt%, 31wt%, 31.5wt%, 32wt%, 32.5wt%, 33wt%, 33.5wt%, 34wt%, 34.5wt%, 35wt%.

[0069] In a specific embodiment of the present application, the mass of the ultraviolet-visible wavelength conversion particles relative to the mass of the ultraviolet-visible wavelength conversion layer is 3-7wt%, for example, 3wt%, 3.1wt%, 3.2wt%, 3.3wt%, 3.4wt%, 3.5wt%, 3.6wt%, 3.7wt%, 3.8wt%, 3.9wt%, 4wt%, 4.1wt%, 4.2wt%, 4.3wt%, 4.4wt%, 4.5wt%, 4.6wt%, 4.7wt%, 4.8wt%, 4.9wt%, 5wt%, 5.1wt%, 5.2wt%, 5.3wt%, 5.4wt%, 5.5wt%, 5.6wt%, 5.7wt%, 5. 8wt%, 5.9wt%, 6wt%, 6.1wt%, 6.2wt%, 6.3wt%, 6.4wt%, 6.5wt%, 6.6wt%, 6.7wt%, 6.8wt%, 6.9wt%, 7wt%.

[0070] In a specific embodiment of the present application, the high refractive index micro-nanoparticles are selected from one or more materials such as titanium dioxide, silicon dioxide, zinc oxide, silicon carbide, silicon nitride, zinc sulfide, aluminum oxide, iron oxide, boron nitride, magnesium oxide, barium sulfate, barium carbonate and aluminum silicate.

[0071] In a specific embodiment of the present application, the ultraviolet-visible wavelength conversion particles are selected from one or more of fluorescein isothiocyanate, Oregon green, carboxy naphthofluorescein, rhodamine, oxadiazoles and their derivatives, triazoles and their derivatives, rhodamine and their derivatives, coumarin derivatives, 1,8-naphthalimide derivatives, pyrazoline derivatives, triphenylamine derivatives, porphyrin compounds, carbazole, pyrazine, thiazole derivatives and perylene derivatives.

[0072] In a specific embodiment of the present application, the modifier is selected from one or more of sodium secondary alkyl sulfonate, sodium fatty acid methyl ester ethoxylate sulfonate, sodium fatty acid methyl ester sulfonate, sodium dioctyl succinate sulfonate, sodium dodecylbenzene sulfonate, sodium glycocholate, and sodium taurocholate.

[0073] In a specific embodiment of the present application, the organic polymer is selected from one or more of polyacrylic acid, polytetrafluoroethylene, polyvinylidene fluoride, polydimethylsiloxane, polyurethane, polypropylene, polyethylene and polyamide.

[0074] In a specific embodiment of the present application, the dye is selected from one or more of medium chrome yellow, red iron oxide, iron yellow, iron blue, iron green, iron black, toluidine red, scarlet powder, and molybdenum chrome orange.

[0075] The present application provides a fabric, which can be prepared by the above-mentioned preparation method, and includes: a fabric substrate; a high reflection layer; an ultraviolet-visible wavelength conversion layer; a visible colored layer; and other functional layers.

[0076] In a specific embodiment of the present application, the fabric has a high reflective layer, and the thickness of the high reflective layer is 15 to 400 μm, for example, it can be 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm, 160 μm, 165 μm, 170 μm, 175 μm, 180 μm, 185 μm, 190 μm, 1 95μm, 200μm, 205μm, 210μm, 215μm, 220μm, 225μm, 230μm, 235μm, 240μm, 245 μm, 250μm, 255μm, 260μm, 265μm, 270μm, 275μm, 280μm, 285μm, 290μm, 295μm, 300μm, 305μm, 310μm, 315μm, 320μm, 325μm, 330μm, 335μm, 340μm, 345μm, 350 μm, 355μm, 360μm, 365μm, 370μm, 375μm, 380μm, 385μm, 390μm, 395μm, 400μm.

[0077] In a specific embodiment of the present application, the fabric has an ultraviolet-visible wavelength conversion layer, and the thickness of the ultraviolet-visible wavelength conversion layer is 15 to 400 μm, for example, it can be 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm, 160 μm, 165 μm, 170 μm, 175 μm, 180 μm, 185 μm, 1 90μm, 195μm, 200μm, 205μm, 210μm, 215μm, 220μm, 225μm, 230μm, 235μm, 240μm , 245μm, 250μm, 255μm, 260μm, 265μm, 270μm, 275μm, 280μm, 285μm, 290μm, 295 μm, 300μm, 305μm, 310μm, 315μm, 320μm, 325μm, 330μm, 335μm, 340μm, 345μm, 3 50μm, 355μm, 360μm, 365μm, 370μm, 375μm, 380μm, 385μm, 390μm, 395μm, 400μm.

[0078] In a specific embodiment of the present application, the fabric has a visible colored layer, and the thickness of the visible colored layer is 15 to 400 μm, for example, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm, 160 μm, 165 μm, 170 μm, 175 μm, 180 μm, 185 μm, 190 μm, 195μm, 200μm, 205μm, 210μm, 215μm, 220μm, 225μm, 230μm, 235μm, 240μm, 245 μm, 250μm, 255μm, 260μm, 265μm, 270μm, 275μm, 280μm, 285μm, 290μm, 295μm, 300μm, 305μm, 310μm, 315μm, 320μm, 325μm, 330μm, 335μm, 340μm, 345μm, 350 μm, 355μm, 360μm, 365μm, 370μm, 375μm, 380μm, 385μm, 390μm, 395μm, 400μm.

[0079] In a specific embodiment of the present application, the fabric has other functional layers, and the thickness of the other functional layers is 15 to 400 μm, for example, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, 125 μm, 130 μm, 135 μm, 140 μm, 145 μm, 150 μm, 155 μm, 160 μm, 165 μm, 170 μm, 175 μm, 180 μm, 185 μm, 190 μm, 195μm, 200μm, 205μm, 210μm, 215μm, 220μm, 225μm, 230μm, 235μm, 240μm, 245 μm, 250μm, 255μm, 260μm, 265μm, 270μm, 275μm, 280μm, 285μm, 290μm, 295μm, 300μm, 305μm, 310μm, 315μm, 320μm, 325μm, 330μm, 335μm, 340μm, 345μm, 350 μm, 355μm, 360μm, 365μm, 370μm, 375μm, 380μm, 385μm, 390μm, 395μm, 400μm.

[0080] In a specific embodiment of the present application, the structure of the fabric is a fabric substrate, a high reflective layer, an ultraviolet-visible wavelength conversion layer, a visible colored layer and other functional layers arranged in sequence from bottom to top.

[0081] Example

[0082] In the following examples, the names and sources of the raw materials are as follows:

[0083] Organic polymer: polyvinylidene fluoride-hexafluoropropylene P (VDF-HFP) (brand: Arkema, model: 2801, density 1.78g / mL)

[0084] High refractive index micro-nano particles: titanium dioxide nanoparticles TiO2 (purchased from Shanghai Liangjiang Titanium Dioxide Chemical Products Co., Ltd., model: A200, density 4.26 g / cm 3 )

[0085] Organic solvent: N,N-dimethylformamide DMF (brand: Merck, purity: 99%)

[0086] Modifier: Sodium dodecylbenzene sulfonate SDBS (Brand: McLean, Purity: AR, 90.0%)

[0087] UV-Visible wavelength conversion particles: fluorescein isothiocyanate (brand: Ecosol / Youso, model: CBS-X), rhodamine (brand: McLean, model: R817327, purity: 99%), 7-hydroxy-4-methylcoumarin (brand: McLean, model: H964241, purity: 98%), 7-amino-4-trifluoromethylcoumarin (brand: McLean, model: A801693, purity: 99%)

[0088] Waterproof agent for fabrics (Brand: Daxin, Model: ADX-A1000)

[0089] Fabric dye (Brand: Ranbar, Model: Ranbar Blue 2N)

[0090] Fabric (purchased from Linyi New Cotton Textile Co., Ltd., polyester-cotton canvas)

[0091] Example 1

[0092] The embodiment of the present application provides a method for preparing a multi-level structure zero-energy cooling fabric based on wavelength conversion, comprising the following steps:

[0093] First, 10 g of P(VDF-HFP) and 120 g of DMF were stirred at 55° C. for 30 minutes to obtain a P(VDF-HFP)-DMF blend solution, and 1.26 g of TiO2 nanoparticles were added and dispersed uniformly by magnetic stirring. In addition, 0.076 g of SDBS was added to the P(VDF-HFP)-DMF blend solution, and the mixture was stirred at 55° C. for 2 hours to obtain a high reflection layer solution, and the obtained high reflection layer solution was subjected to 20 minutes of ultrasonic treatment.

[0094] The obtained high reflective layer solution was scraped on the fabric surface for multiple times using a scraper with a thickness of 100 μm, and dried and cured under constant temperature and humidity conditions of room temperature 25°C and relative humidity 50% until the thickness of the high reflective layer reached 300 μm. Figure 3 As shown in SEM, the mass of the added TiO2 nanoparticles accounts for 5% of the mass of the high reflective layer.

[0095] Similarly, 10 g of P(VdF-HFP) powder and 120 g of DMF solvent were stirred at 55° C. for 30 minutes to obtain a P(VdF-HFP)-DMF blend solution, 0.5 g of fluorescein isothiocyanate and 0.07 g of SDBS were added to the blend solution and stirred for 2 hours to obtain a UV-visible wavelength conversion layer solution, and the obtained UV-visible wavelength conversion layer solution was subjected to 20 minutes of ultrasonic treatment.

[0096] The obtained ultraviolet-visible wavelength conversion layer solution was scraped onto the high reflective layer using a scraper with a thickness of 40 μm, and dried and cured under constant temperature and humidity conditions of 25° C. and 50% relative humidity to obtain an ultraviolet-visible wavelength conversion layer with a thickness of 40 μm. The mass of the added fluorescein isothiocyanate accounted for 5% of the mass of the ultraviolet-visible wavelength conversion layer.

[0097] 5 g of hydrophobic material for fabric was sprayed on the UV-visible wavelength conversion layer and dried in a blast oven at 120° C. for 2 h to obtain a Figure 1 The multi-level structure zero-energy cooling fabric based on wavelength conversion with a waterproof layer is shown.

[0098] Example 2

[0099] The difference between this embodiment and embodiment 1 is that 4.21 g of TiO2 nanoparticles are added, accounting for 15% of the mass of the high reflective layer.

[0100] Example 3

[0101] The difference between this embodiment and embodiment 1 is that the amount of TiO2 nanoparticles added is 7.95 g, accounting for 25% of the mass of the high reflective layer. Figure 3 As shown in SEM picture.

[0102] Example 4

[0103] The difference between the embodiment of the present application and embodiment 3 is that the amount of TiO2 nanoparticles added is 7.95 g, accounting for 35% of the mass of the high reflective layer.

[0104] Example 5

[0105] The difference between this embodiment and embodiment 3 is that the thickness of the high reflection layer is 200 μm.

[0106] Example 6

[0107] The difference between this embodiment and embodiment 3 is that the thickness of the high reflection layer is 100 μm.

[0108] Example 7

[0109] The difference between this embodiment and embodiment 3 is that the thickness of the high reflection layer is 400 μm.

[0110] Example 8

[0111] The difference between this embodiment and embodiment 3 is that the thickness of the ultraviolet-visible wavelength conversion layer is 20 μm.

[0112] Example 9

[0113] The difference between this embodiment and embodiment 3 is that the thickness of the ultraviolet-visible wavelength conversion layer is 60 μm.

[0114] Example 10

[0115] The difference between this embodiment and embodiment 3 is that 0.3 g of fluorescein isothiocyanate is added, which accounts for 3% of the mass of the ultraviolet-visible wavelength conversion layer.

[0116] Embodiment 11

[0117] The difference between this embodiment and embodiment 3 is that 0.7 g of fluorescein isothiocyanate is added, accounting for 7% of the mass of the ultraviolet-visible wavelength conversion layer.

[0118] Example 12

[0119] The difference between this embodiment and embodiment 3 is that the hydrophobic material is not sprayed on the surface of the ultraviolet-visible wavelength conversion layer.

[0120] Embodiment 13

[0121] The difference between this embodiment and embodiment 3 is that fluorescein isothiocyanate is replaced by rhodamine.

[0122] Embodiment 14

[0123] The difference between this embodiment and embodiment 3 is that fluorescein isothiocyanate is replaced by 7-hydroxy-4-methylcoumarin.

[0124] Embodiment 15

[0125] The difference between this embodiment and embodiment 3 is that fluorescein isothiocyanate is replaced by 7-amino-4-trifluoromethylcoumarin.

[0126] Example 16

[0127] The difference between this embodiment and embodiment 3 is that the particle size of titanium dioxide is 100 nm.

[0128] Comparative Example 1

[0129] The difference between this embodiment and embodiment 3 is that when preparing the ultraviolet-visible wavelength conversion layer solution, no ultraviolet-visible wavelength conversion particles are added.

[0130] Comparative Example 2

[0131] The difference between this embodiment and embodiment 3 is that there is no ultraviolet-visible wavelength conversion layer, and ultraviolet-visible wavelength conversion particles are mixed into the high reflection layer.

[0132] Experimental Example 1

[0133] The ultraviolet-visible wavelength conversion particles used in Example 3 are tested using an ultraviolet-visible spectrophotometer. The ultraviolet-visible wavelength conversion particles are dissolved or dispersed in an aqueous solution and added to a cuvette. The solution in the cuvette should be 2 / 3-4 / 5 of the height of the cuvette and should not be too full. The light source of the spectrophotometer emits incident light of a fixed wavelength band, and the detector can convert the optical signal into an electrical signal, and amplify the signal through a signal display system, thereby obtaining ultraviolet-visible wavelength conversion data such as Figure 2 shown.

[0134] Experimental Example 2

[0135] The emissivity of the multi-level structure zero-energy cooling fabrics prepared in Examples 1-14, Comparative Example 1, and Comparative Example 2 in the solar radiation (0.3-2.5 μm) band was tested using a UV-VIS-NIR spectrophotometer combined with an integrating sphere; the morphology of the multi-level structure zero-energy cooling fabrics was tested using a scanning electron microscope. The hydrophobicity of the multi-level structure zero-energy cooling fabrics was tested using a contact angle meter, and the test results are shown in Table 1, where the reflectivity of Examples 3, 5, 6, and 7 is plotted as shown in Table 1. Figure 4 shown.

[0136] Table 1 Comparison of fabric properties

[0137]

[0138]

[0139] Note: The symbol “\” indicates that the structure or particle is not involved in the embodiment or comparative example.

[0140] It can be seen from Table 1 that the embodiment 3 has the highest reflectivity in the sunlight band, and the embodiments and comparative examples other than embodiment 12 have good waterproof performance.

[0141] It can be seen from Examples 1-4 that when the mass proportion of titanium dioxide relative to the high reflective layer is 25%, the reflectivity in the solar band is the highest; when the mass proportion of titanium dioxide is less than 25%, as the mass proportion decreases, the reflectivity in the solar band decreases significantly; and when the mass proportion of titanium dioxide is greater than 25%, as the mass proportion increases, the reflectivity in the solar band does not change significantly, and even a slight decrease occurs.

[0142] It can be seen from Examples 3, 5, 6, and 7 that when the thickness of the high-reflection layer is 300 , the reflectivity in the sunlight band is the highest; when the thickness of the high-reflection layer is less than 300, as the thickness of the high-reflection layer decreases, the reflectivity in the sunlight band decreases, and when the thickness of the high-reflection layer decreases to below 200, the reflectivity in the sunlight band decreases more significantly; when the thickness of the high-reflection layer is greater than 300, as the thickness of the high-reflection layer increases, the reflectivity in the sunlight band does not change significantly.

[0143] It can be seen from Examples 3, 8, and 9 that when the thickness of the ultraviolet-visible wavelength conversion layer is 40 μm, the reflectivity in the sunlight band is the highest; when the thickness of the ultraviolet-visible wavelength conversion layer decreases or increases, the reflectivity in the sunlight band decreases slightly.

[0144] It can be seen from Examples 3, 10, 11 and Comparative Example 1 that when the mass proportion of the ultraviolet-visible wavelength conversion particles relative to the high reflective layer is 5%, the sunlight wavelength reflectivity is the highest; when the mass proportion of the ultraviolet-visible wavelength conversion particles relative to the high reflective layer gradually decreases or increases, the sunlight wavelength reflectivity will decrease, among which, when the mass proportion of the ultraviolet-visible wavelength conversion particles relative to the high reflective layer decreases, the sunlight wavelength reflectivity decreases more significantly.

[0145] It can be seen from Examples 3 and 12 that when the hydrophobic material is not sprayed on the fabric surface, the water contact angle of the fabric is the lowest and the hydrophobic performance is poor. The hydrophobic material has a good waterproof effect on the fabric.

[0146] It can be seen from Examples 3, 13, 14, 15 and Comparative Example 1 that when fluorescein isothiocyanate is replaced with rhodamine, the sunlight wavelength reflectivity will be significantly reduced, but rhodamine, 7-hydroxy-4-methylcoumarin and 7-amino-4-trifluoromethylcoumarin as UV-visible wavelength conversion particles still have a certain improvement in the sunlight wavelength reflectivity, and the sunlight wavelength reflectivity is significantly higher than the fabric in Comparative Example 1 without adding UV-visible wavelength conversion particles.

[0147] It can be seen from Examples 3 and 16 that a decrease in the particle size of titanium dioxide will slightly reduce the reflectivity of the sunlight wavelength.

[0148] It can be seen from Example 3 and Comparative Example 1 that when there is no ultraviolet-visible wavelength conversion layer structure and the entire fabric does not have any ultraviolet-visible wavelength conversion particles, the reflectivity in the sunlight band is significantly reduced.

[0149] It can be seen from Example 3 and Comparative Example 2 that when the ultraviolet-visible wavelength conversion particles are added to the high-reflection layer, the reflectivity of the ultraviolet-visible wavelength conversion particles to the wavelength of sunlight is not significantly improved.

[0150] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0151] The above-described embodiments only express several implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the present application. It should be pointed out that, for a person of ordinary skill in the art, several variations and improvements can be made without departing from the concept of the present application, and these all belong to the protection scope of the present application. Therefore, the protection scope of the patent of the present application shall be subject to the attached claims.

Claims

1. A method for preparing a fabric, comprising the steps of: dissolving the organic polymer in an organic solvent to obtain a conjugate solution; Adding high refractive index micro-nano particles and a modifier to the conjugate solution in sequence to obtain a high reflective layer solution; Adding UV-visible wavelength conversion particles and a modifier to the conjugate solution in sequence to obtain a UV-visible wavelength conversion layer solution; The high reflection layer solution and the ultraviolet-visible wavelength conversion layer solution are subjected to ultrasonic treatment respectively; Applying the ultrasonically treated high-reflection layer solution on the fabric by scraping, and forming a high-reflection layer after drying and curing; The ultraviolet-visible wavelength conversion layer solution after ultrasonic treatment is scraped onto the high reflection layer, and after drying and curing, an ultraviolet-visible wavelength conversion layer is formed.

2. The method according to claim 1, wherein: A dye is also scraped on the ultraviolet-visible wavelength conversion layer, and the coating forms a visible colored layer after drying and curing.

3. The method according to claim 1, wherein: One or more of waterproof coating, acid-proof coating, alkali-proof coating and anti-corrosion coating are scraped on the ultraviolet-visible wavelength conversion layer to form other functional layers.

4. The method according to claim 2, wherein: One or more of waterproof coating, acid-proof coating, alkali-proof coating and anti-corrosion coating are scraped on the visible colored layer to form other functional layers.

5. A fabric comprising: Fabric substrate; Highly reflective layer; UV-visible wavelength conversion layer; Colored layers are visible; as well as Other functional layers.

6. The fabric according to claim 5, wherein: The thickness of the high reflective layer is 15 to 400 μm; The thickness of the ultraviolet-visible wavelength conversion layer is 15 to 400 μm; The thickness of the visible colored layer is 15 to 400 μm; The thickness of the other functional layer is 15-400 μm.

7. The fabric according to claim 5, wherein: The textile substrate, the high reflective layer, the ultraviolet-visible wavelength conversion layer, the visible colored layer and other functional layers are arranged in sequence from bottom to top.

8. The fabric according to any one of claims 5 to 7, which is prepared by the method according to any one of claims 1 to 4.

9. A fabric, wherein: Prepared by the method according to any one of claims 1 to 4.

10. Use of the fabric according to any one of claims 5 to 9 for cooling in automobile sunshade cloth, tent cloth, glass house sunshade cloth and building decorative cloth.

Citation Information

Patent Citations

  • Ultraviolet-proof black-out cloth

    CN215970400U

  • Shading and cooling fabric

    CN218906556U

  • Novel black-out cloth with multi-layer structure

    CN219214343U

  • Flame-retardant black-out cloth

    CN220264803U